ANALISIS PERILAKU KONSUMEN TERHADAP MINAT PENGGUNAAN PINJAMAN ONLINE PADA SANTRI PESANTREN X DI KOTA TASIKMALAYA - Setyasari, Untung Eko; Subarkah, Cici (ACITYA: Jurnal Vokasi Bisnis Digital, Akuntansi Lembaga Keuangan Syariah dan Usaha Perjalanan Wisata, 2024)
Analysis of Consumer Behavior on Interest in Using Online Loans among Islamic Boarding School X Students in Tasikmalaya City. Online loans (pinjol) are one proof of the development of the fintech world. This development then gave rise to the phenomenon of the pros and cons of online loans. This is what underlies this research which aims to analyze consumer behavior regarding interest in using online loans among students at one of the Islamic boarding schools in Tasikmalaya City. The research method used is a quantitative approach, with nonprobability sampling, namely an accidental sampling technique. The data analysis techniques used in this research are validity test, reliability test, simple linear regression, coefficient of determination and t test (partial). The results of research with 73 respondents show that overall consumer behavior is in the good category and interest in using online loans among Islamic Boarding School X students in Tasikmalaya City is in the neutral category. The influence of consumer behavior on interest in using online loans and hypothesis testing has been carried out by looking at the calculated Sig t numbers in the coefficients table output. The calculated Sig t value is 0.016 < 0.01 so that H0 is rejected and Ha is accepted, which means that the initial alternative hypothesis proposed can be accepted. So consumer behavior influences interest in using online loans. The results of calculating the coefficient of determination value show that consumer behavior has an influence of 7.9% on interest in using online loans, while the remaining 82.1% is influenced by other variables not studied.